Research on the HTML5 Application Runtime Environment for Mobile Terminal - Gang Lu; Honghui Ou; Baiqing Liang; Rongrong Li (Dianxin kexue)
A new generation of Web HTML5 standard has become a general technical standard for mobile internet application platform in the future，and mobile Web application based on HTML5 is becoming a new form of application. The HTML5 runtime environment is an important carrier of mobile Web applications with the core position in ecosystem of the Web application. Firstly，the status of mobile Web applications and development trends were analyzed. Then，the function structure of application of HTML5 runtime environment was researched，and related key technologies were analyzed. Also，the solution of HTML5 runtime environment for mobile terminal was proposed.